Implementasi Metode Takrir dalam Meningkatkan Hafalan Al-Qur'an: Implementation of the Takrir Method in Enhancing Quran Memorization - Ridiawati, Ridiawati; Komarudin, Komarudin; Rochman, Asep Saepul; Hariyanto, Teguh; Jaelani, Deny Ahmad (Risalah Kharisma, 2025)
This study examines the effectiveness of the takrir method in enhancing Qur'an memorization at SMP IT Rohmatul Ummah. The takrir method, meaning "repetition" in Arabic, is a widely used technique in memorization learning, where students repeatedly recite verses to strengthen their memory. This research aims to understand the implementation of the takrir method in the school setting and evaluate both supporting factors and challenges faced in its application. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation involving the school principal, teachers, and students. The findings indicate that the takrir method is effective in facilitating students' memorization processes; however, certain challenges must be addressed, such as the need for strict supervision of school regulations, teacher readiness as mentors, and internal support in the form of student motivation as well as external support from the family environment. The implications of this study highlight that the success of the takrir method is greatly influenced by the synergy between school and family in creating a conducive environment for memorization. Recommendations include strengthening coordination between the school and parents and providing better teacher training to ensure that the takrir method can optimally benefit Qur'anic education in schools.